Cholangiocarcinoma in a Bitch - Multimodal Diagnosis - Paiva, Felipe Noleto de [UNESP]; Oliveira, Gabriella Santos; Souza, Shayne Abranches de; Oliveira, Priscila Cardim de; Costa, Thiago Souza; Fernandes, Julio Israel (Univ Fed Rio Grande Do Sul, 2023)
Background: Hepatic tumors of primary origin account for 0.6% to 2.9% of cases in canine species, less common than hepatic metastases. The hepatic tumors are divided into hepatocellular tumors, neuroendocrine tumors, bile duct tumors or cholangiocarcinomas, and mesenchymal tumors. Cholangiocarcinomas, are classified according to their origin, being intrahepatic, extrahepatic, or gallbladder type. Cholangiocarcinomas are considered rare in dogs and cats with a ratio of 29% to 71% compared to hepatocellular carcinomas, accounting for 9% of the hepatic tumors. The present study aims to describe a case of cholangiocarcinoma in a bitch, focusing on the diagnostic approach. Case: A 10-year-old castrated bitch Poodle was attended presenting hypoglycemia and seizure crisis. The patient had previous exams of hemogram and serum biochemical profile, showing a discrete increase of the hepatic enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST), besides hypoglycemia. Previous ultrasound exam revealed the presence of a hepatic mass located between the right and square lobes, immeasurable, and significant splenomegaly. Abdominal palpation revealed the presence of immeasurable abdominal formation of undetermined origin. Abdominal computerized tomography (CT), glycemic curve, and insulin dosage were requested. Tomography exam showed an increase in hepatic volume with the presence of a heterogeneous formation in the right lateral lobe topography; increase in spleen dimensions and the presence of multiple nodules; and the presence of a nodule in the right lung, at the caudal thoracic region. The glycemic curve showed acute variations, and insulin dosage was between normal values. The animal was referred for surgery, as in abdominocentesis, it was observed the presence of hemorrhagic fluid, confirming active bleeding by ultrasonography. The owners chose for euthanasia. In the post-mortem evaluation the main lesion was confirmed of hepatic origin, with a massive, irregular, cavitary presentation, involving multiple hepatic lobes, and a single nodule was observed in the right caudal lobe of the right lung. Histopathological evaluation was considered inconclusive. Immunohistochemistry was performed and the association of the immunohistochemical profile with the morphological characteristics indicated diagnosis of cholangiocarcinoma. Discussion: The related symptomatology, in hepatic neoplasms, is generally considered non-specific, with reports of lethargy, vomiting, dyspnea, anorexia and weight loss, however, the dog in this study presented a unique manifestation of hypoglycemia and one episode of convulsive crisis resulting from it. The clinical manifestation observed was extremely unspecific making initial diagnosis difficult. The ultrasonographic examination was effective in evidencing the abdominal mass. In addition, abdominal CT was also performed, which confirmed the hepatic origin, detailing the macroscopic aspect. Biochemical analyses of ALT and AST showed a discrete increase. Biochemical changes may occur in dogs with hepatic neoplasms, although they are not specific. Functional pancreatic beta-cell tumors producing insulin are the most common cause of paraneoplastic hypoglycemia, although in the case the insulin dosage was within normal limits. In cases of non-islet cell tumor the mechanism is frequently associated with the production of insulin-like growth factor (IGF). In most cases the definitive diagnosis of cholangiocarcinoma can be obtained by histopathological examination, although in the present report the result obtained was inconclusive, requiring an immunohistochemical examination. Due to the aggressive and metastatic character of this neoplastic type, early detection becomes extremely important in order to maximize therapeutic chances, however, diagnosis may be difficult.
Keywords: hepatic neoplasm; dog; biliary carcinoma; immunohistochemistry